EFEK PENAMBAHAN BUBUK TEMULAWAK (Curcuma xanthorrhiza ) PADA PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Zulkhasyni; Ahmad, Nasir; Badriyyah, Alya; Yulfiperius; Syukhriani, Silvy (University of Prof. Dr. Hazairin, SH, 2024)
This research aims to determine the effect of adding ginger powder to artificial feed on the growth of tilapia (Oreochromis niloticus). This research was carried out from May to June 2023 for 60 days located in Margasakti Village, Padang Jaya District. The test fish used were tilapia (Oreochromis niloticus) with a size of 10-12 cm/head. The design used was a Completely Randomized Design (CRD), which consisted of 4 treatments with 6 repetitions to obtain 24 experimental units. treatment 1 (P1): without adding ginger powder, treatment 2 (P2): 1.5 gram ginger powder, treatment 3 (P3): 1.8 gram ginger powder, treatment 4 (P4): 2.1 gram ginger powder. The data obtained was tested by analysis of variance at the 5% and 1% levels, while to determine the best effect of adding ginger powder, a 5% BNT (Least Significant Difference) further test was carried out. The parameters observed were fish growth, which included absolute length and weight, feed conversion, feed efficiency and survival of the test fish. The results of the research showed that the addition of ginger powder to the growth of tilapia had a very significant effect on the growth in absolute length, absolute weight, feed conversion and feed efficiency. The addition of good ginger powder is the addition of 1.8 grams of ginger powder and the addition of 2.1 grams of ginger powder with survival reaching 100%. In cultivation development, you can use the addition of 1.8 grams of ginger powder.